Differential Regulation of Ciliary Neurotrophic Factor and Its Receptor in the Rat Hippocampus in Response to Kainic Acid-induced Excitotoxicity - Choi, Jeong-Sun; Kim, Seong Yun; Park, Hyun-Jung; Cha, Jung-Ho; Choi, Yun-Sik; Chung, Jin-Woong; Chun, Myung-Hoon; Lee, Mun-Yong (Molecules and cells, 2004)
We analyzed the changes in expression of ciliary neurotrophic factor (CNTF) and its receptor, ligand-binding subunit a (CNTFRa), in the hippocampus following intraperitoneal administration of a convulsant dose of kainic acid (KA). Immunohistochemistry and immunoblotting showed that CNTF levels rose dramatically between day 1 and day 10, and that the CNTF was located in reactive astrocytes. In contrast, upregulation of CNTFRalpha mRNA, occurred in neurons as well as astrocytes. A rapid, and short-lived (3 h-2 d) increase in CNTFRalpha was also observed in the more resistant granule cells and CA2 pyramidal neurons. The increase in astrocytes was detected by day 1 and was sustained for more than 5 d. These results show that CNTF and CNTFRalpha are differentially regulated in hippocampal neurons and reactive astrocytes following KA injection, indicating that these proteins may be involved in the regulation of astrocyte and neuronal degenerative responses.